Tinjauan Yuridis Penerapan Hukuman Terhadap Pelaku Tindak Pidana Penganiayaan Hewan - Carmelito Michael Admaderiam; Trias Saputra (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to find out and provide an explanation of how criminal sanctions are applied to protect animal abuse in Indonesia and to find out and provide an explanation of how criminal sanctions are imposed on perpetrators of animal abuse. This research uses the Normative Juridical method. Legal sources are collected from primary data such as laws and Supreme Court decisions, secondary data such as books and scientific journals, and tertiary data such as legal dictionaries. Data collection techniques are through literature study, while legal data processing is through presentation, interpretation, analysis and systematization of applicable laws. Legal analysis is carried out comprehensively and descriptively to explain the problems studied. The results of this research show that the Indonesian Government, through the Criminal Law Law and Law No. 18 of 2009 which was amended by Law No. 41 of 2014, emphasizes the importance of treating animals well. These laws aim to protect animals and ensure their use is done ethically and responsibly. With the main principle of Respectful Treatment, Animals must be treated well and not harmed. Animal Welfare: Animals' physical, mental and emotional needs must be considered, including providing a safe environment and sufficient food. Avoiding Overexploitation, Animals should not be used excessively for the benefit of humans. Protection from Inappropriate Treatment, Animals must be protected from violence and torture. This law aims to maintain animal welfare, respect ethical values, maintain ecosystem balance, and protect public health from diseases that can spread from animals.